Transcranial deep-tissue phototherapy for Alzheimer's disease using low-dose X-ray-activated long-afterglow scintillators - Ma, Mengmeng (2023)
Non-invasive phototherapy has been emerging as an ambitious tactic for suppression of amyloid-β (Aβ) self-assembly against Alzheimer's disease (AD). However, it remains a daunting challenge to develop efficient photosensitizers for Aβ oxygenation that are activatable in a deep brain tissue through the scalp and skull, while reducing side effects on normal tissues. Here, we report an Aβ targeted, low-dose X-ray-excitable long-afterglow scintillator (ScNPs@RB/Ab) for efficient deep-brain phototherapy. We demonstrate that the as-synthesized ScNPs@RB/Ab is capable of converting X-rays into visible light to activate the photosensitizers of rose bengal (RB) for Aβ oxygenation through the scalp and skull. We show that the ScNPs@RB/Ab persistently emitting visible luminescence can substantially minimize the risk of excessive X-ray exposure dosage. Importantly, peptide KLVFFAED-functionalized ScNPs@RB/Ab shows a blood-brain barrier permeability. In vivo experimental results validated that ScNPs@RB/Ab alleviated Aβ burden and slowed cognitive decline in triple-transgenic AD model mice at extremely low X-ray doses without side effects. Our study paves a new pathway to develop high-efficiency transcranial AD phototherapy. STATEMENT OF SIGNIFICANCE: Non-invasive phototherapy has been emerging as an ambitious tactic for suppression of amyloid-β (Aβ) self-assembly against Alzheimer's disease (AD). However, it remains a daunting challenge to develop efficient photosensitizers for Aβ oxygenation that are activatable in a deep brain tissue through the scalp and skull, while reducing side effects on normal tissues. Herein, we report an Aβ targeted, low-dose X-ray-excitable long-afterglow scintillators (ScNPs@RB/Ab) for efficient deep-brain phototherapy. In vivo experimental results validated that ScNPs@RB/Ab alleviated Aβ burden and slowed cognitive decline in triple-transgenic AD model mice at extremely low X-ray doses without side effects.